An Arabidopsis mutant that requires increased calcium for potassium nutrition and salt tolerance - Liu, Jiping (National Academy of Sciences, 1997)
Potassium (K(+)) nutrition and salt tolerance are key factors controlling plant productivity. However, the mechanisms by which plants regulate K(+) nutrition and salt tolerance are poorly understood. We report here the identification of an Arabidopsis thaliana mutant, sos3 (salt-overly-sensitive 3), which is hypersensitive to Na(+) and Li(+) stresses. The mutation is recessive and is in a nuclear gene that maps to chromosome V. The sos3 mutation also renders the plant unable to grow on low K(+). Surprisingly, increased extracellular Ca(2+) suppresses the growth defect of sos3 plants on low K(+) or 50 mM NaCl. In contrast, high concentrations of external Ca(2+) do not rescue the growth of the salt-hypersensitive sos1 mutant on low K(+) or 50 mM NaCl. Under NaCl stress, sos3 seedlings accumulated more Na(+) and less K(+) than the wild type. Increased external Ca(2+) improved K(+)/Na(+) selectivity of both sos3 and wild-type plants. However, this Ca(2+) effect in sos3 is more than twice as much as that in the wild type. In addition to defining the first plant mutant with an altered calcium response, these results demonstrate that the SOS3 locus is essential for K(+) nutrition, K(+)/Na(+) selectivity, and salt tolerance in higher plants.